2022
DOI: 10.2147/copd.s353441
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Exacerbations Associated with Suboptimal Peak Inspiratory Flow Among Stable Outpatients with COPD

Abstract: Purpose A suboptimal peak inspiratory flow (PIF) against a dry powder inhaler (DPI) may result in ineffective inhalation of medications, which may affect outcomes. The primary objective of this study was to examine the association between PIF status and COPD exacerbations among outpatients with moderate to very severe COPD. Patients and Methods This was a prospective, observational study of patients from 7 US outpatient centers. PIF was measured using an inspiratory flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…SGRQ and CAT provide a comprehensive assessment of the COPD-specifc health status of patients [1]; therefore, a signifcant diference between CAT scores in participants with sPIF and those with oPIF suggests that suboptimal PIF may be generally associated with poor health status. A signifcant association between sPIF and high levels of dyspnea and poor COPD-related health status was also recently demonstrated in outpatients with stable moderateto-very severe COPD and sPIF [36].…”
Section: Discussionmentioning
confidence: 65%
“…SGRQ and CAT provide a comprehensive assessment of the COPD-specifc health status of patients [1]; therefore, a signifcant diference between CAT scores in participants with sPIF and those with oPIF suggests that suboptimal PIF may be generally associated with poor health status. A signifcant association between sPIF and high levels of dyspnea and poor COPD-related health status was also recently demonstrated in outpatients with stable moderateto-very severe COPD and sPIF [36].…”
Section: Discussionmentioning
confidence: 65%
“…A prospective, observational study by Mahler et al [7 ▪▪ ] of patients from seven US outpatient centers, measured PIF using the In-Check DIAL G16 inspiratory flow meter set to medium low resistance. Patients were classified by suboptimal (<60 l/min) or optimal PIF (≥60 l/min).…”
Section: Why Is Peak Inspiratory Flow Important?mentioning
confidence: 99%
“…For clinical applications, an optimal PIFr ⩾60 L/min has been proposed for DPIs with low to medium-high resistance and ⩾30 L/min for high-resistance DPIs ( 40 , 42 , 43 ). Patients with suboptimal PIFr may be unable to completely inhale the powder medication out of the DPI, thereby leading to reduced delivery of the fine-particle dose to the lower respiratory tract, adversely affecting outcomes ( 44 46 ).…”
Section: Patient Factors To Consider When Selecting An Inhaled Delive...mentioning
confidence: 99%
“…Moreover, patients with suboptimal PIFr have greater symptom burden (as measured using the mMRC scale [ P = 0.003] and the COPD Assessment Test [ P < 0.01]) and a shorter time to first exacerbation compared with patients with optimal PIFr ( P = 0.048) ( 46 ). In addition, in a cross-sectional, multicountry study of 1,434 patients with COPD using DPIs for maintenance therapy, Leving and colleagues ( 30 ) showed that patients with suboptimal PIFr had higher medication costs compared with those with optimal PIFr (cost ratio, 1.07 [95% CI, 1.01–1.14]).…”
Section: Patient Factors To Consider When Selecting An Inhaled Delive...mentioning
confidence: 99%